Modelling and spectroscopic studies of 1-hydroxyethylidene-1,1-diphosphonic acid and its interaction with hydroxyapatite as a model of bone - Van Rooyen, Petrus H. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.